Effect of bilayer numbers on structural, mechanical, tribological and corrosion properties of TiO2–SiO2 multilayer film-coated β-type Ti45Nb alloys. Issue 2 (15th January 2023) - Çomaklı, Onur; Yazıcı, Mustafa; Demir, Merve; Yetim, Ali Fatih; Çelik, Ayhan
Abstract: Protective films with excellent tribological performance and good corrosion resistance are needed in general because titanium implants are used in aggressive environments and always suffer from severe wear and corrosion. In this study, TiO2 –SiO2 multilayer films were deposited with different numbers of bilayers (2, 4, and 8) on β-type Ti45Nb alloy substrates by physical vapour deposition. The influence of number of bilayers on microstructure, wettability, mechanical features, tribological performance and electrochemical behaviour of TiO2 –SiO2 multilayer films were comparatively observed via XRD, XPS, SEM, AFM, nanoindentation tester, contact angle measurement system, reciprocating tribo-tester, and electrochemical corrosion media. The surface hardness, wear and corrosion resistance values of multilayer film-coated substrates were higher than the untreated substrate values. These properties and adhesion resistance and hydrophobicity of coated samples also increased with increase in number of bilayers due to the smaller grain size, increased layered interfaces and high structural density.